Anti-heat shock protein 70 kDa and 90 kDa antibodies in serum of patients with rheumatoid arthritis. Issue 5 (1st May 1999) - Hayem, G; De Bandt, M; Palazzo, E; Roux, S; Combe, B; Eliaou, J F; Sany, J; Kahn, M F; Meyer, O
Abstract : OBJECTIVES: Stress proteins (HSPs) are highly conserved immunodominant antigens found in various species. The purpose of this study was to assess the prevalence and prognostic significance of antibodies to HSC 70 kDa and HSP 90 kDa in three groups of patients with longstanding rheumatoid arthritis (RA) defined based on the severity of articular erosions. METHODS: 73 patients with longstanding (> 6 years) RA whose HLA-DR genotype was known were divided in three groups according to Larsen's score and compared with 47 recent onset (<1 year) RA patients and with control groups composed of patients with other inflammatory diseases (n=137) or of normal controls (n=48). IgGs and IgMs to HSC 70 kDa and HSP 90 kDa were determined using an ELISA with purified bovine HSC 70kDa or HSP 90 kDa. RESULTS: Concentrations of IgGs and IgMs to HSC 70 were significantly increased in 41.1% and 42.5% of longstanding RA patients, respectively. Corresponding figures for IgGs and IgMs to HSP 90 were 39.7% and 56%. IgMs to HSC 70 and HSP 90 were less frequent in recent onset RA (19% and 13% respectively). Among the groups with other inflammatory diseases, only the MCTD group exhibited high frequencies of IgGs to HSC 70 (80%) and HSP 90 (85%). DRB1*0401 positive RA patients (n=23) were not more likely to have increased concentrations of antibodies to HSC 70 kDa or HSP 90 kDa than other RA patients (DR4 positive but DRB1*0401 negative, or DR1 positive, n=31; or negative for both DR4 and DR1, n=14). IgGs to HSP 90 kDa were significantly more frequent (p<0.05) in longstanding RA patients whose Larsen's score was 4 or more (57%) than in those whose Larsen's score was 2 or 3 (39.4%) or less than 2 (16%). No associations were found between Larsen's score and IgGs or IgMs to HSC 70 kDa or IgMs to HSP 90 kDa. A significant correlation was demonstrated between IgGs to HSP 90 kDa and two other serological markers for RA, rheumatoid factor, and anti-Sa antibody; there were no correlations with antikeratin antibody, antiperinuclear factor, or anti-RA 33. CONCLUSION: IgGs to HSP 90 kDa are most common in longstanding RA patients with articular erosions, suggesting that they may be related to the articular prognosis in RA